The influence of marketing mix strategy on sales volume at PT.Jaya Anugrah Sukses Abadi Medan - Jonner Lumban Gaol (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2021)
The purpose of this research is to analyze the influence of marketing mix strategies covering products, prices, promotions, and distribution channels on increasing sales volume at PT. Jaya Anugrah Success Abadi and to analyze the variables of the most dominant marketing mix strategy affects the increase in sales volume. The results of data analysis with multiple linear regression analysis methods show that products (X1), price (X2), promotion (X3) and Distribution Channel (X4) are jointly influential and significant to sales volume in PT.Jaya Anugrah Sukses Abadi Medan with regression coefficient X1 (b1) = 0.270, regression coefficient X2 (b2) = -0.220, regression coefficient X3 (b3) = 0.491 and coefficient of regression X4 (b4) = 0.273. F counting tests were obtained at 35,348 greater than Ftabel's 2,584. T test results showed for product = 2,564, price = -2,807, promotion = 4,683 and distribution channels = 2,430, the most dominant variables affected were the perception of promotional variables and the determination test results showed that 70.57% of variations of the marketing mix were influenced by all four independent variables, while 29.41% were other factors not studied in this study.